PsycEXTRA Dataset 2007
DOI: 10.1037/e526322010-003
|View full text |Cite
|
Sign up to set email alerts
|

Supershrinks: What's the secret of their success?

Abstract: Clients of the best therapists improve at a rate at least 50 per cent higher and drop out at a rate at least 50 per cent lower than those of average clinicians. What is the key to superior performance? Are 'supershrinks' made or born? Is it a matter of temperament or training? Have they discovered a secret unknown to other clinicians or are their superior results simply a fluke, more measurement error than reality? We know that who provides the therapy is a much more important determinant of success than what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 0 publications
0
66
0
4
Order By: Relevance
“…But there's hope for us. There is evidence that extraordinary psychotherapists—those with the best results, who are able to develop and maintain strong therapeutic relationships—are not born or made in graduate school, they are relentlessly self‐upgrading (Miller, Hubble, & Duncan, 2007). They engage continuously in a special kind of self‐development: deliberative practice (Ericsson, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…But there's hope for us. There is evidence that extraordinary psychotherapists—those with the best results, who are able to develop and maintain strong therapeutic relationships—are not born or made in graduate school, they are relentlessly self‐upgrading (Miller, Hubble, & Duncan, 2007). They engage continuously in a special kind of self‐development: deliberative practice (Ericsson, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In their studies of the very best therapists, whom they termed "supershrinks, " Miller, Hubble, and Duncan (2008) found that they"without exception possess a keen 'situational awareness': They are observant, alert and attentive. They compare new information constantly with what they already know" (p. 19).…”
Section: Self-regulated Learning As a Vehicle For Lifelong Learningmentioning
confidence: 99%
“…Therapists were experienced as having a willingness to help and listen. Miller, Duncan, & Hubble, (2008) The team are aware that the environment is a challenge with rooms often on the small side for larger family or network meetings and general issues about room availability which can impact on the therapist's ability to be flexible around appointment times. This has been fed back to hospital management.…”
Section: Discussionmentioning
confidence: 99%